Women of Childbearing Age in Healthy Village Makassar City: Health Belief Model Approach - Risna Ayu Rahmadani; Apik Indarty Moedjiono; Saifuddin Sirajudin (Humanistic Network for Science and Technology (HNST), 2019)
An unwanted pregnancy is the effect of stopping use of contraception, which can lead to unsafe abortion and maternal death. This study aims to analyze the determinants of pregnancy intentions in women of childbearing age in Pai healthy village of Makassar. The research used quantitative cross sectional study design. The research sample consisted of 170 women of childbearing age who were selected using a purposive sampling technique. Data were analyzed using the chi square test, and multiple logistic regressions. The results showed that there was an influence of age, husband's support, health worker support, threat perception, perceived suseptibility, perceived benefits, and perceived barriers to pregnancy intentions (p